Kurdistan Nurses' Feelings and Experiences About Patients' Death in ICUs: A Case Study in Kurdistan Region, Iraq - Muaf Abdulla Karim; Forough Rafii; Alireza Nikbakht Nasrabadi (Iran University of Medical Sciences, 2017)
Background: As members of the health care team in Intensive Care Units (ICUs), nurses play a vital role in caring for critically ill patients. The demands of caring in such an environment put the nurses under huge pressure, especially when their patients die. This qualitative study explores the feelings and experiences of Kurdish intensive care nurses providing care for dying patients in the ICU.  Methods: This qualitative study used inductive content analysis. The data were collected through in-depth semi-structured interviews with a purposive sample of 10 Kurdish registered nurses working in adult ICUs of Rezgary and Hawler Teaching hospitals (Erbil, Iraq). Results: Three main categories, including emotional burden, encountering with obstacles, and personal growth emerged. In spite of their emotional burden and also the pressure imposed by heavy workload, the nurses' personal growth was enhanced by the self-confidence and spiritual satisfaction they acquired by caring for ill and end stage patients and their families.  Conclusion: Nurses' religious beliefs and their special cultural background could partly modify their negative feelings and perceptions. However, in the long run, dealing with these pressures and negative environmental and organizational inhibitors could lead to burnout. All potential sources of emotional and psychological burden in these ICUs need to be minimized by appropriate planning. Nurses' and their special cultural background could partly modify their negative feelings and perceptions.